Effect of Movement Control Order to Emergency Department Visit in A Teaching University Hospital in Malaysia During COVID-19 - King, Wong Chui; Jaafar, Mohd Johar; Haji Manaf, Mohd Rizal; Isa, Mohd Hisham; Saiboon, Ismail Mohd (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Implementation of lockdown was identified as a factor that affects the utilization of Emergency Department (ED) globally during COVID-19 pandemic. Objective: To compare the ED utilization rate based on different triage acuity during movement control order (MCO) of COVID-19 pandemic at a teaching university hospital in the capital of Malaysia, Kuala Lumpur. Methods: This retrospective study included patients presented to ED during MCO i.e. March 18 to June 9 of 2020) and a similar period of pre-pandemic for comparison. Patients were randomized and segregated to different triage categories. Other outcomes determined include demographics, comorbidities, type of cases, mode of arrival and disposition. The data were analysed using chi-square test. Results: Distribution of cases based on triage acuity were consistent between MCO and pre-pandemic period (p=0.063). Lowest triage acuity (TG), had the highest utilization, followed by second triage acuity (TY) and finally highest triage acuity (TR). For TG, adult and elderly (p<0.001), married (p<0.001) and presence of comorbidities groups (p<0.001) were the main presenters and were more likely to require admission during MCO (p=0.01). The TY categories were higher amongst adult and elderly (p<0.001) and married individuals (p=0.003) during MCO. Paediatric age-group was significantly low in both lower triage acuity categories. In term of ambulance arrival, majority of patients belongs to the TY acuity category (p=0.005). TR category patients did not demonstrate significant changes. Conclusion: MCO implementation during COVID-19 pandemic did not change the rate of patient presentation based on triage acuity. However, pattern of cases in the lower triage acuity showed some differences. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 313-319